Terapeutyczna moc ruchu i zabawy = The Therapeutic Power of Play and Outdoor Games - Wiatrowska, Leokadia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Play and outdoor games are basic forms of any child`s physical activity. It is through them that personal growth - the key existential task of every human being - is facilitated. Pupils who, as a result of polyetiological conditioning, suffer from growth disorders, require extra help and support on these fronts. Their activity needs stimulating through play and outdoor games which, in ways acceptable to the child, should result in the pupil`s qualitative and quantitative growth.
Keywords: rozwój; zmiana rozwojowa; oddziaływania wychowawczo-terapeutyczne; ruch; zabawy; aktywność dziecka; growth; developmental change; therapeutic impact; play; outdoor games; child`s activity